Osseous resective surgery with and without fibre retention technique in the treatment of shallow intrabony defects: a split‐mouth randomized clinical trial. (14th January 2015) - Aimetti, Mario; Mariani, Giulia Maria; Ferrarotti, Francesco; Ercoli, Elena; Audagna, Martina; Bignardi, Cristina; Romano, Federica
Abstract Aim The aim of this split‐mouth clinical trial was to compare the effectiveness of Apically Positioned Flap with Fibre Retention Osseous Resective Surgery (FibReORS) or Osseous Resective Surgery (ORS) in the treatment of periodontal pockets associated with intrabony defects ≤3 mm at posterior natural teeth. Materials and Methods Twenty‐six posterior sextants requiring osseous resective surgery were selected in 13 chronic periodontitis patients: 13 sextants were randomly assigned to ORS and 13 to FibReORS. Clinical evaluation of probing depth (PD), gingival recession and clinical attachment level was performed at baseline, 6 and 12 months postoperatively. Periapical radiographs were taken prior and after surgical treatment, at 6‐ and 12‐month follow‐up. Results Ostectomy amounted to 1.0 ± 0.3 mm in the ORS group and to 0.4 ± 0.2 mm in the FibReORS group. At 12‐month examination PD changes did not significantly differ between the experimental groups. ORS group showed significantly (p < 0.001) greater clinical attachment loss (2.2 ± 1.0 mm versus 1.0 ± 0.6 mm), radiographic bone resorption (0.43 ± 0.08 mm versus 0.13 ± 0.09 mm) and post‐operative patient discomfort compared to FibReORS. Conclusion FibReORS resulted in similar PD reduction, but less ostectomy, clinical attachment loss and patient morbidity compared to ORS.